Let's simplify each expression one by one and check their coefficients.
-
Expression: \(-2m + 5m\) \[ -2m + 5m = (5 - 2)m = 3m \] Coefficient: \(3\)
-
Expression: \(-5m + 2m\) \[ -5m + 2m = (2 - 5)m = -3m \] Coefficient: \(-3\)
-
Expression: \(5m - 2m\) \[ 5m - 2m = (5 - 2)m = 3m \] Coefficient: \(3\)
-
Expression: \(2m + 5m\) \[ 2m + 5m = (2 + 5)m = 7m \] Coefficient: \(7\)
From the simplifications, the expression \(-5m + 2m\) results in a coefficient of \(-3\).
Thus, the answer is: \(-5m + 2m\) has a coefficient of \(-3\).